169k views
4 votes
Solve the literal equation −cy+2=3d+7y for y.

1 Answer

4 votes

Answer:

y = (2-3d)/(7+c)

Explanation:

-cy + 2 = 3d + 7y

To solve this equation in terms of y, we must first move all of the terms containing a y to one side of the equation and move all of the other terms to the other side.

Our first step is going to be to add cy to both sides of the equation.

- cy + cy + 2 = 3d + 7y + cy

2 = 3d + 7y + cy

Next, we can subtract 3d from both sides of the equation.

2 - 3d = 7y + cy

Next, we can factor out a y from the right side of the equation.

2 - 3d = y (7 + c)

Finally, we can divide both sides by the quantity (7+c) to get the y alone on the right side of the equation.

(2-3d)/(7+c) = y

Therefore, your answer is y = (2-3d)/(7+c).

Hope this helps!

User Stratis
by
4.8k points